Expatriation in Malaysia: Predictors of Cross-Cultural Adjustment among Hotel Expatriates - Haslina Halim; Hassan Abu Bakar; Bahtiar Mohamad (International Journal of Supply Chain Management, 2019)
The stress experienced by expatriates is usually caused by the inability to adjust to the host culture, which largely results from their lack of social skills needed in dealing with the new cultural environment. Thus, the main purpose of this study is to identify the predictors of cross-cultural adjustment among expatriates in Malaysia, by focusing on expatriates in hotel industry. The findings from the study could help clarify the over generalization made of data which are usually based on certain locations and groups of expatriates. Two hundred and three expatriates participated in the study. Personality, language ability, previous international experience, training, human resource support, social support, culture distance and family adjustment were analyzed using the multiple regression analysis to determine the predictors of adjustment. The data, which was drawn from a drop and collect method, self-administered questionnaire, revealed that social support and family adjustment were the most influential predictors of hotel expatriate adjustment. The findings also suggest that over generalizations of findings across disciplines are rather inappropriate. Detail discussions on the methods, findings, limitations, and suggestions for future research are presented in the paper.